A Survey of Increased Infectious Risk Donor Utilization in Canadian Transplant Programs. Issue 2 (February 2016) - Kumar, Deepali; Humar, Atul; Kim, S. Joseph; Kiberd, Bryce
Abstract : Background: Donors at increased risk of transmitting viral infections are a potential source of transplantable organs. Studies demonstrate that organs from increased risk donors (IRDs) are associated with excellent outcomes. However, considerable variation in practice likely exists. Methods: We performed a cross-country survey of Canadian Organ Transplant centers to determine organ utilization practices from IRDs. Results: Of 40 surveys sent to transplant programs across Canada, 24 (60%) were returned. Of those, 60.9% (15/24) had a formal policy for their use, and 21.7% (5/24) had never accepted an IRD. Only 41.7% (10/24) had access to timely nucleic acid testing (NAT), and respondents were more likely to accept IRD if NAT was available. For example the likelihood of using organs from an intravenous drug user increased from 12.5% (4/24) with serology negative donors to 70.8% (17/24) if NAT was available and the donor had no increased activity within the window period ( P < 0.001). Only 37.5% (9/24) discussed the use of IRDs with candidates at listing, with 54.2% (13/24) stating that having a standardized consent would increase utilization of IRDs. Conclusions: The results suggest that availability of NAT would increase IRD utilization. In addition written policies and procedures on IRD use and the consent process would be recommended in many Canadian centers. Abstract : Supplemental digital content is available in the text.